The Association between Sex Hormones, Pubertal Milestones and Benzophenone-3 Exposure, Measured by Urinary Biomarker or Questionnaire. Issue 10 (3rd October 2022) - Giannini, Courtney M; Huang, Bin; Chandler, Donald W; Fassler, Cecily S; Schwartz, Richard C; Biro, Frank M; Pinney, Susan M
ABSTRACT: Experimental studies have suggested benzophenone-3 (BP-3), a sunscreen ingredient, may have endocrine-disrupting properties. A cohort of girls were recruited at ages 6–7 years and returned semi-annually for pubertal maturation staging, provided blood for serum hormone analyses [estradiol, estrone, testosterone, dehydroepiandrosterone-sulfate (DHEA-S)], and urine to measure BP-3 concentrations. We found a significant negative linear association between amount of reported sunscreen use and testosterone levels at the onset of puberty (N = 157, adjusted β = −0.0163, 97.5% CI:-0.0300, -0.0026). The 2nd quartile of the BP-3 biomarker had earlier thelarche compared to the 1st quartile (N = 282, adjusted HR = 1.584, 97.5% CI:1.038, 2.415). Results suggest that higher report of sunscreen use may be associated with lower testosterone levels at thelarche and a non-linear relationship between the BP-3 urinary biomarker and onset of puberty, although the clinical significance of the finding is limited and may be a random effect. Improved methods of BP-3 exposure characterization are needed.